Reliable Intent Detection in Public Service Chatbots Using Hybrid IndoBERT and Bidirectional Long Short-Term Memory with Confidence-Based Decision Strategy - Satya, Barka; Kurniawan, Mei Parwanto; Indryatmoko, Toto; As'adurrofiq, As'adurrofiq (Informatika, Universitas Jenderal Soedirman, 2026)
The rapid digitalization of public services has increased the demand for intelligent information systems capable of providing accurate and responsive assistance to citizens on a 24/7 basis. However, many existing public service chatbots still rely on rule-based mechanisms or single-model natural language processing (NLP) approaches, which often fail to handle linguistic variations, informal expressions, and ambiguous user queries. This study proposes a Hybrid Natural Language Understanding (NLU) architecture that integrates a fine-tuned IndoBERT model with a Bidirectional Long Short-Term Memory (BiLSTM) network to improve intent detection performance in public service chatbots. To enhance system reliability, a confidence-based decision-making mechanism is introduced, enabling the system to dynamically select the most reliable prediction or activate a fallback pattern-matching module when confidence thresholds are not met. The proposed approach was evaluated on a custom dataset comprising 53 public service intents, spanning formal and informal Indonesian language use. Experimental results demonstrate that the hybrid architecture achieves an intent classification accuracy of 86.8%, outperforming single-model approaches while maintaining an acceptable response time for practical deployment, particularly in public service scenarios where accuracy and reliability are prioritized over response speed. Furthermore, integrating a continuous learning mechanism enables the system to adapt to low-confidence queries over time, thereby improving robustness in real-world applications. These findings indicate that hybrid NLP architectures with confidence-aware decision mechanisms offer a practical and scalable solution for intelligent public service chatbots.